2021
DOI: 10.1186/s12872-021-02107-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and risk factors of postoperative in-hospital mortality following surgical repair of Stanford type A acute aortic dissection

Abstract: Background To investigate the clinical features of patients with Stanford type A acute aortic dissection (AAD) and analyze the risk factors affecting postoperative in-hospital mortality rate. Methods The demographic and clinical data were retrospectively collected and analyzed from 118 AAD patients admitted to the Affiliated Hospital of Hangzhou Normal University from June 2016 to April 2019. All patients underwent surgical treatment and were grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…The survival profile of Stanford type A AD patients is unfavorable 7,8,29,30 . Hence, identifying novel biomarkers to estimate the mortality risk and perform early intervention is still necessary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The survival profile of Stanford type A AD patients is unfavorable 7,8,29,30 . Hence, identifying novel biomarkers to estimate the mortality risk and perform early intervention is still necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was observed that only Th17 cells were positively related to CRP and Ddimer in Stanford type A AD patients, which could be explained as that: (a) Th17 cells upregulated various pro-inflammatory cytokines (such as interleukin (IL)-17, IL-21, and granulocyte macrophagecolony stimulating factor (GM-CSF)) to promote the neutrophil The survival profile of Stanford type A AD patients is unfavorable. 7,8,29,30 Hence, identifying novel biomarkers to estimate the mortality risk and perform early intervention is still necessary. Th17 cells are previously observed to positively correlate with the 3-year mortality rate in Stanford type B AD patients, while its clinical value in Stanford type A AD patients remains exclusive.…”
Section: Crp and D-dimer Are Two Well-established Biomarkers In Acutementioning
confidence: 99%
See 2 more Smart Citations
“…The post-discharge mortality in individuals with ATAAD is independently predicted by relatively high WBC on admission, according to Zhang et al ( 27 ). Ke et al also said that increased WBC can be employed as supplementary markers for postoperative in-hospital death with ATAAD ( 28 ). Elevated preoperative WBC was associated with a higher risk of death following an ATAAD procedure in this research, and this could be caused by inflammation from a vascular intima rupture, just as the difference in WBC between the two groups was statistically significant, which is in line with the findings of the outcomes of past experiments ( 29 ).…”
Section: Discussionmentioning
confidence: 99%